2017
DOI: 10.2169/internalmedicine.56.7738
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone-induced Eosinophilic Pleurisy

Abstract: The patient was a 69-year-old man with idiopathic pulmonary fibrosis who was taking pirfenidone. After 7 weeks of treatment, he suffered from left-sided eosinophilic pleurisy. Medical thoracoscopy was performed and the histopathological examination of the parietal pleura revealed the massive infiltration of eosinophils and lymphoid follicles. After stopping pirfenidone therapy, the patient's pleural effusion disappeared without additional treatment, and never recurred. This is the first case report of pirfenid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In addition, EPEs are likely to be associated with connective tissue disease, infection resulting from bacteria, mycobacteria, parasites, fungi, and pulmonary thromboembolism, [4,7] and in our case, the autoimmune profile, the relevant clinical and laboratory findings were normal. Recently, certain drugs containing warfarin, pirfenidone as well as methimazole are recently reported that are related to the development of EPE, [8][9][10] but our patient was taking oral isoniazid and rifampin for 6 months and denied other suspicious drugs intake.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, EPEs are likely to be associated with connective tissue disease, infection resulting from bacteria, mycobacteria, parasites, fungi, and pulmonary thromboembolism, [4,7] and in our case, the autoimmune profile, the relevant clinical and laboratory findings were normal. Recently, certain drugs containing warfarin, pirfenidone as well as methimazole are recently reported that are related to the development of EPE, [8][9][10] but our patient was taking oral isoniazid and rifampin for 6 months and denied other suspicious drugs intake.…”
Section: Discussionmentioning
confidence: 66%
“…As for other etiologies of eosinophilic pleural effusion, connective tissue diseases including rheumatoid arthritis and ulcerative colitis, pulmonary embolism, benign asbestos pleural effusion and pancreatic diseases including acute pancreatitis account for a few percent of the etiologies of eosinophilic pleural effusions [ 1 , [9] , [10] , [11] ]. Importantly, in previous studies, around 20% of the cases were of unknown etiology, some of which might have been occult, rare differential diagnoses including hypereosinophilic syndrome, eosinophilic granulomatous polyangiitis, chronic eosinophilic pneumonia, chronic myeloid leukemia, human T-cell leukemia virus type 1 infection, drug-induced pleuritis, and parasitic infestations [ 1 , [12] , [13] , [14] , [15] , [16] , [17] , [18] ], although they should be diagnosed because they require specific treatments. Thus, it is necessary to have an approach to the investigation of the different causal etiologies of eosinophilic pleurisy taking into account their frequency, importance, and the ease of performance and invasiveness of the examinations.…”
Section: Discussionmentioning
confidence: 99%